Investigation of e-sports attitudes among prospective physical education and sports teachers - Vural, Engin; Toçoğlu, Sinem; Kiratli, Tuncay; Yildirim, Yavuz; Saritemur, Büşra (SPORT TK-EuroAmerican Journal of Sport Sciences, 2026)
This study aimed to examine the e-sports attitudes of prospective physical education and sports teachers. A total of 304 participants, including 154 (50.7%) females and 150 (49.3%) males, with a mean age of X̄ = 21.17±2.10, studying in the Department of Physical Education and Sports Teaching at three different state universities, were included in the study. A Personal Information Form developed by the researchers and the “E-Sports Attitude Scale” were used to assess e-sports attitudes. According to the study results, a statistically significant difference was found in mean e-sports attitude scores according to the gender variable (p<0.05). It was determined that there were no statistically significant differences in mean e-sports attitude scores according to class level (p>0.05). However, statistically significant differences were observed in mean e-sports attitude scores based on the duration of gameplay (p<0.05). In conclusion, it was found that males exhibited more positive attitudes toward e-sports, grade level did not significantly affect e-sports attitudes, and participants’ attitudes toward e-sports became more positive as gameplay duration increased. Future studies may consider exploring other demographic factors influencing e-sports attitudes, which are expected to contribute further to the literature.